Adjusting adjustment: Supply response and the sequencing of reform policies - Jürgen Zattler (Intereconomics, 1993)
The classical approach towards adjustment has proved to have considerable shortcomings, particularly in connection with supply response issues and the conditions for re-establishing sustainable growth. The following article concludes that sustainable stabilisation and adjustment require a revised sequencing of policies, and outlines the main consequences of this for donor assistance strategies.
Keywords: 330; Development Strategy